Water availability and substrate in the emergency and initial development of Bauhinia scandens L.1 - Jeromini, Tatiane Sanches [UNESP]; Silva, Givanildo Zildo Da; Martins, Cibele Chalita [UNESP]; Neves, Breno Rosa [UNESP] (Universidade Federal de Viçosa, 2021)
Bauhinia scandens is an ornamental plant and it has anti-tumor properties. The demand for seedlings of this species makes it necessary to know about the germinative behavior of seeds and the initial growth of seedlings. The objective of the present work was to determine the type of substrate and moistening conditions that are more favorable to the emergence and development of seedlings of B. scandens. B. scandens seeds were disposed on three substrates: sand, vermiculite, and commercial substrate, maintained at four levels of moistening 25, 50, 75, and 100% of the water holding capacity of the substrate and kept in a greenhouse for 60 days. The following parameters were evaluated: emergence, speed index, average time, number of leaves, length of aerial part and root, diameter of neck, fresh and dry mass of aerial part and root. The analysis of variance was performed in a completely randomized design, in a 3 X 4 factorial scheme, with four replications of 25 seeds. The sowing of B. scandens should be carried out initially in vermiculite with a holding capacity of 100% until the establishment of the seedling emergence and then transplanted to commercial substrate keeping between 50 and 75% holding capacity.
Keywords: seedlings; wetting; vine-bauhinia; ornamental plant; production